2019
DOI: 10.1016/j.neuroimage.2019.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Is removal of weak connections necessary for graph-theoretical analysis of dense weighted structural connectomes from diffusion MRI?

Abstract: Recent advances in diffusion MRI tractography permit the generation of dense weighted structural connectomes that offer greater insight into brain organization. However, these efforts are hampered by the lack of consensus on how to extract topological measures from the resulting graphs. Here we evaluate the common practice of removing the graphs' weak connections, which is primarily intended to eliminate spurious connections and emphasize strong connections. Because this processing step requires arbitrary or h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
83
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 66 publications
(117 reference statements)
9
83
1
Order By: Relevance
“…Our results are in line with recent diffusion tensor imaging study, where the preserving of weak connections on calculation of graph connectivity metrics was advocated for Civier et al (2019), and with earlier fMRI study where thresholding has been shown to lead to inconsistent results (Garrison et al, 2015). The results suggest that common practice in research to eliminate weak connections may lead to missing important information.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are in line with recent diffusion tensor imaging study, where the preserving of weak connections on calculation of graph connectivity metrics was advocated for Civier et al (2019), and with earlier fMRI study where thresholding has been shown to lead to inconsistent results (Garrison et al, 2015). The results suggest that common practice in research to eliminate weak connections may lead to missing important information.…”
Section: Discussionsupporting
confidence: 90%
“…In combination with results from multiple approaches indicating pervasive degeneration of the brain's white matter connections with adult age (Burzynska et al, 2010;Cox et al, 2016;Salat, 2011), our finding that the strongest age-associations fell between 50% and 95% network sparsity, and that the profile of age-associations within the discarded connections were predominantly null across sparsities is consistent with: 1) prior evidence that the human brain is likely to have a connection density of ~30% (Roberts et al, 2017); 2) that probabilistic tractography fundamentally over-estimates the number of connections (Roberts et al, 2017), and; 3) that these spurious connections add noise to the signal (Jbabdi and Johansen-Berg, 2011). Moreover, our results are inconsistent with previous reports that topological network properties of connectomes are not significantly altered by the removal of weak connections (Civier et al, 2019).…”
Section: Discussioncontrasting
confidence: 79%
“…A recent population-based atlas of white matter connectivity, constructed by manually labelling 40 major streamline clusters (Yeh et al, 2018), shows promise in validating connectivity but is limited to a small proportion of possible network connections.In the absence of a comprehensive map of connectivity and to meet a demand for more principled network denoising approaches (de Reus and van den Heuvel, 2013;Maier-Hein et al, 2017;Van Wijk et al, 2010), researchers have introduced inferential methods to identify and discard potentially spurious connections. Some researchers have advocated using raw (unthresholded) matrices without removal of any connections on the basis that topological network properties are not significantly altered by the inclusion of weak connections (Civier et al, 2019). However, many network studies have employed thresholding strategies, such as, absolute-thresholding which applies a uniform threshold to retain only connections above a set weight (Hagmann et al, 2007), and density-thresholding which applies a (relative) threshold on the connection weights such that the weakest connections are removed to match the same number of connections across subjects (Rubinov and Sporns, 2010).…”
mentioning
confidence: 99%
“…Although we explored multiple brain network reconstruction pipelines, we were not primarily concerned with which mapping techniques produced connectomes with the highest predictive utility. The choice of parcellation schemes [70] and whether or not to threshold structural connectomes [71,72] are both complex open questions that fall outside the scope of this work. We also note that white matter tractography algorithms are susceptible to a number of known biases that could potentially impact our results [73].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%